AON-induced splice-switching and DMPK pre-mRNA degradation as potential therapeutic approaches for Myotonic Dystrophy type 1. Issue 5 (22nd January 2020) - Stepniak-Konieczna, Ewa; Konieczny, Patryk; Cywoniuk, Piotr; Dluzewska, Julia; Sobczak, Krzysztof
Abstract: Expansion of an unstable CTG repeat in the 3′UTR of the DMPK gene causes Myotonic Dystrophy type 1 (DM1). CUG-expanded DMPK transcripts (CUG exp ) sequester Muscleblind-like (MBNL) alternative splicing regulators in ribonuclear inclusions (foci), leading to abnormalities in RNA processing and splicing. To alleviate the burden of CUG exp, we tested therapeutic approach utilizing antisense oligonucleotides (AONs)-mediated DMPK splice-switching and degradation of mutated pre-mRNA. Experimental design involved: (i) skipping of selected constitutive exons to induce frameshifting and decay of toxic mRNAs by an RNA surveillance mechanism, and (ii) exclusion of the alternative exon 15 (e15) carrying CUG exp from DMPK mRNA. While first strategy failed to stimulate DMPK mRNA decay, exclusion of e15 enhanced DMPK nuclear export but triggered accumulation of potentially harmful spliced out pre-mRNA fragment containing CUG exp . Neutralization of this fragment with antisense gapmers complementary to intronic sequences preceding e15 failed to diminish DM1-specific spliceopathy due to AONs' chemistry-related toxicity. However, intronic gapmers alone reduced the level of DMPK mRNA and mitigated DM1-related cellular phenotypes including spliceopathy and nuclear foci. Thus, a combination of the correct chemistry and experimental approach should be carefully considered to design a safe AON-based therapeutic strategy for DM1.